2015
DOI: 10.1188/15.cjon.19-04ap
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining Coagulation Blood Samples From Central Venous Access Devices: A Review of the Literature

Abstract: The only method for obtaining reliable coagulation test results from central venous access devices is the flush then waste/discard method. This method has only been studied with peripherally inserted central catheters. Additional randomized, controlled trials with larger sample sizes are needed to determine the most appropriate method for drawing coagulation test results from central venous access devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…From systematic reviews of 11 studies [16], they find that sample sizes in each study were too small (N range from 12-53) (72 sample sizes in this study). Pearson correlations, or mean difference comparisons, may have statistical differences but cannot be interpreted as clinical judgment, making them difficult to apply in actual practice.…”
Section: Discussionmentioning
confidence: 75%
“…From systematic reviews of 11 studies [16], they find that sample sizes in each study were too small (N range from 12-53) (72 sample sizes in this study). Pearson correlations, or mean difference comparisons, may have statistical differences but cannot be interpreted as clinical judgment, making them difficult to apply in actual practice.…”
Section: Discussionmentioning
confidence: 75%
“…From systematic reviews of 11 studies 16 , they nd that sample sizes in each study were too small (N range from 12-53) (72 sample sizes in this study). Pearson correlations, or mean difference comparisons, may have statistical differences but cannot be interpreted as clinical judgment, making them di cult to apply in real practice.…”
Section: The Accuracymentioning
confidence: 84%
“…The existing literature has described the methods of blood sampling from a A comparative study on coagulation and hematologic laboratory techniques for blood sampling using the push-pull method from a CVC versus venipuncture CVAD, which mainly including the discard method, reinfusion method and push-pull method, and the discard method is the most common technique, however, when drawing blood specimens in this manner, an adequate volume of blood is usually discarded to avoid altering the test results because of the presence of infusion substances in the discarded sample. For the discard method, studies reported that discard volumes ranging from 2 to 25 mL, 2 and this wide variation could produce hospital-acquired anemia. 3,4 The reinfusion method is similar to the discard method, but the original discard sample is reinfused in the end.…”
Section: Introductionmentioning
confidence: 99%